Предмет: Алгебра,
автор: anton012008
(5y-3x)*(25y²+15yx+9x²)=
(1) 125y³-27x³
(2) 25y²-30yx+9x²
(3) 25y²+30yx+9x²
(4) 125y³+27x³
(5) 25y³-9x³
Ответы
Автор ответа:
0
(5y-3x)·(25y²+15yx+9x²) = 5y·(25y²+15yx+9x²)-3x·(25y²+15yx+9x²) = 125y³+75xy²+45x²y-75xy²-45x²y-27x³ = 125y³-27x³
Похожие вопросы
Предмет: Русский язык,
автор: Милка200511
Предмет: Английский язык,
автор: nastyaslastya12
Предмет: Русский язык,
автор: Pavel5hak
Предмет: Українська література,
автор: SashaAndi
Предмет: Геометрия,
автор: nikitavolk007